Variasi Aeromonas Pada Ikan Sidat (Anguilla sp.) yang dilalulintaskan Melalui Bandar Udara Palu - Irmawan Syafitrianto; Amal Aqmal; Mohammad Nur Halik Lande (Biogenesis: Jurnal Ilmiah Biologi, 2016)
Central Sulawesi is a province produce eels (Anguilla marmorata) in Indonesia. Eels is the one commodity that has a high economic value. In the last years, eels trading traffic through the airport had increased. Fish health status to be one of the important issues in trade of eels. Genus Aeromonas is disease-causing pathogen on eels and as the etiologic agent responsible for a variety of infectious complications pathogenic bacteria. The purpose of this study is identify the various species of the genus Aeromonas on the eels which are traffic through Mutiara Sis Al jufri Airport Palu. This observation have been from April to December 2014. Specimens Anguilla sp. was obtained from supplier in the Palu city. Laboratory examination performed use conventional methods (Biochemistry) and performed in Microbiology Laboratory of Fish Quarantine Palu. The result showed from 396 eels have been identified, 128 of them are of the genus Aeromonas (32.32%). Aeromonas were identified some species among other: Aeromonas sobria, Aeromonas hydrophilla, and Aeromonas caviae. A.sobria is higher percentage in April and August 2014 (57,14%), A. hydrophilla in December 2014 (92,85%), and A. caviae August 2014 (21,43%). The existence of pathogenic bacteria in eels this should be a concern to prevent widespread dissemination through trade traffic.